O gênero masculino na docência da Educação Infantil no contexto de Humaitá/AM - Mendonça, José Edilson de Lima (Brasil, 2021)
This Course Completion work is the result of an experience lived in the supervised internship in early childhood education and a scientific initiation project within the scope of the degree course in Pedagogy at UFAM/IEAA, whose objective was to verify indices of prejudice related to the male gender in early childhood education from the narratives of men (students and graduates) of the IEAA Pedagogy Course. The subjects chosen to be part of this research were teachers/students from the Licentiate Degree in Pedagogy at the IEAA/UFAM and students from the pedagogy course who have already gone through the Supervised Internship in Early Childhood Education. Regarding the research method, it was chosen to use the qualitative approach in education, with emphasis on the techniques of narrative interviews, in which a documental survey was also carried out based on official information from the IEAA/UFAM on the number of students - men and women enrolled in the Pedagogy Course since the creation of the course at the IEAA/UFAM. For discussions on gender we have authors who address the issue such as: Louro (1997, 2007), Xavier (2014), Meyer (2007; 2012) among others. On the insertion of women in child education and the teaching profession in Brazil, we will have Vicentini and Lugli (2009), André (2014), Nóvoa (1987), Tardif (1991) and others who discuss the study as support. The results point to prejudices related to the male figure in early childhood education. In the speeches, we identified that even the student has performed all the essential phases in the academy, with theoretical readings and activities inherent to teacher training, going to the internship ends up becoming very difficult. Consequently, no matter how trained and prepared this professional is, we still live in our thoughts rooted in stereotypes, where all men are seen as dangerous and harmful to our children. We understand that social fear is linked to the high rates of child sexual violence committed by men, however, most acts of violence take place within the family, and at school, the men who work receive training and preparation for this, and cannot be “condemned” socially just for being male.